2020
DOI: 10.1177/0954407020957766
|View full text |Cite
|
Sign up to set email alerts
|

Study on tie rod force characteristics in electro-hydraulic power steering system for heavy vehicle

Abstract: The tie rod is one of the key components affecting the steering stability and reliability in the steering system of heavy vehicles. In order to meet the heavy load steering requirements of heavy vehicles, the steering system is universally the electro-hydraulic power steering system (EHPSS). The hydraulic actuators used in the EHPSS are double hydraulic cylinders, which are connected in series and symmetrically installed in this study. The hydraulic drive system in the steering system will affect the steering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In this paper, it assumes that the system energy consumption is the input energy. The system input power P in can be described as 23 :…”
Section: Modeling and Analysismentioning
confidence: 99%
“…In this paper, it assumes that the system energy consumption is the input energy. The system input power P in can be described as 23 :…”
Section: Modeling and Analysismentioning
confidence: 99%
“…Waybase et al [19] found that vibration and fatigue failure were the main causes of tie rod failure. Godase et al [20] and Du et al [21] pointed out that the strength of tie rods is mainly influenced by bending, tension, load, and shear, among which the shear resistance of tie rods is often neglected. And Godase et al found that the geometric parameters of the tie rod, such as its outer diameter and inner diameter, have a significant effect on shear stress.…”
Section: Introductionmentioning
confidence: 99%